Hermann Hesse et l’attractivité du Sud-Tessin - Bertrand Lévy (Territoire en Mouvement)
The article connects an author, Hermann Hesse, with Ticino, the region that he made his own. Noting that all writers’ museums are similar in the material they display and sell, the text develops, from a humanistic geographical perspective, the author’s attachment to places and landscapes, and identifies the basic geographical experience of the visitor. In conclusion it dwells on the visionary role of the artist in terms of future land use conflicts.